Pharmacokinetic evaluation of two pirfenidone formulations in patients with idiopathic pulmonary fibrosis and chronic hypersensitivity pneumonitis. Issue 10 (October 2020) - Barranco-Garduño, Lina Marcela; Buendía-Roldan, Ivette; Rodriguez, Juan Jose; González-Ramírez, Rodrigo; Cervantes-Nevárez, Ariadna N.; Neri-Salvador, Juan Carlos; Carrasco-Portugal, Miriam del Carmen; Castañeda-Hernández, Gilberto; Martinez-Espinosa, Karen; Selman, Moisés; Flores-Murrieta, Francisco Javier
Abstract: Idiopathic pulmonary fibrosis (IPF) is a progressive and fatal disease characterized by an abnormal activation of lung epithelium and fibroblasts, as well as an excessive accumulation of extracellular matrix. Pirfenidone was introduced as a therapeutic option for IPF and chronic hypersensitive pneumonitis (cHP), a related disease. However, high plasma concentrations, which can be achieved even at recommended doses, are frequently associated with adverse events. Hence, an extended release formulation (XP), yielding lower peak plasma concentrations, has been developed. The aim of this study was to compare the pharmacokinetic properties of XP with those of the immediate (IR) formulation in patients with IPF or cHP. Data were analyzed using two pharmacokinetic approaches, conventional non compartmental analysis and a population analysis using the nonlinear mixed effects model technique. Results observed with both approaches were consistent. Drug exposure was similar with both formulations. However, XP exhibited less concentration fluctuations and a longer mean resident time. These results suggest that XP could be a feasible option to reduce adverse events associated to pirfenidone elevated concentrations. Nevertheless, efficacy studies are required to fully document the therapeutic potential of XP. Abstract : Pharmaceutical science; Biological Sciences; Health Sciences; Respiratory System; Pharmacology; Internal Medicine; Pulmonary fibrosis; pirfenidone; population pharmacokinetics.